(untitled) (TEL Tempo, Espaço e Linguagem, 2022)
Despite the constant tensions and denunciations, racial, gender and other violence are not only frequent, but also linked to psychological illness, such as anxiety. This essay aims to propose, based on the clinical experience of the psychologist and first author, decolonial strategies of clinical care for black women who present symptoms of anxiety associated with the intersectionality of gender, race and sexuality, describing experiences that produce psychological suffering reported by women. black women in individual clinical care, identifying beliefs, affections and behaviors related to the anxiety conditions reported by these women in order to present possibilities of action based on the theoretical-methodological approach proposed by the first author.